Facile Synthesis of Sustainable Biomass-Derived Porous Biochars as Promising Electrode Materials for High-Performance Supercapacitor Applications - Ravi Moreno Araujo Pinheiro Lima; Glaydson Simões dos Reis; Mikael Thyrel; Jose Jarib Alcaraz-Espinoza; Sylvia H. Larsson; Helinando Pequeno de Oliveira (Nanomaterials, 2022)
Preparing sustainable and highly efficient biochars as electrodes remains a challenge for building green energy storage devices. In this study, efficient carbon electrodes for supercapacitors were prepared via a facile and sustainable single-step pyrolysis method using spruce bark as a biomass precursor. Herein, biochars activated by KOH and ZnCl2 are explored as templates to be applied to prepare electrodes for supercapacitors. The physical and chemical properties of biochars for application as supercapacitors electrodes were strongly affected by factors such as the nature of the activators and the meso/microporosity, which is a critical condition that affects the internal resistance and diffusive conditions for the charge accumulation process in a real supercapacitor. Results confirmed a lower internal resistance and higher phase angle for devices prepared with ZnCl2 in association with a higher mesoporosity degree and distribution of Zn residues into the matrix. The ZnCl2-activated biochar electrodes’ areal capacitance reached values of 342 mF cm−2 due to the interaction of electrical double-layer capacitance/pseudocapacitance mechanisms in a matrix that favors hydrophilic interactions and the permeation of electrolytes into the pores. The results obtained in this work strongly suggest that the spruce bark can be considered a high-efficiency precursor for biobased electrode preparation to be employed in SCs.